REGULARIZED TRACES OF DIFFERENTIAL OPERATORS - Bayramoglu, Mehmet; Adiguzelov, Ehliman (YILDIZ TECHNICAL UNIV, 2005)
This is a survey article with three parts about the scientific works done on regularized trace which are the generalization of trace formulas of matrices and nuclear operators for differential operators. Here the ssecond part is about [32] and the third part is about [33].
Keywords: Hilbert space; Nuclear operator; Eigenvalue; Spectrum; Adjoint operator; Trace of matrix; Regularized trace; FORMULAS; Engineering